2015
DOI: 10.1186/s12974-015-0359-8
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged diet-induced obesity in mice modifies the inflammatory response and leads to worse outcome after stroke

Abstract: BackgroundObesity increases the risk for ischaemic stroke and is associated with worse outcome clinically and experimentally. Most experimental studies have used genetic models of obesity. Here, a more clinically relevant model, diet-induced obesity, was used to study the impact of obesity over time on the outcome and inflammatory response after stroke.MethodsMale C57BL/6 mice were maintained on a high-fat (60 % fat) or control (12 % fat) diet for 2, 3, 4 and 6 months when experimental stroke was induced by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 39 publications
5
69
3
Order By: Relevance
“…Although not examined in our experiment, the HFD has been shown to increase the extent of damage following ischemic injury in mice 22 and to increase immune cell entry into the central nervous system 4 . We hypothesize that the TWD led to a hyper-responsive immune system that enhanced the hypersensitivity and prolonged the recovery from inflammatory pain induction.…”
Section: Discussionmentioning
confidence: 85%
“…Although not examined in our experiment, the HFD has been shown to increase the extent of damage following ischemic injury in mice 22 and to increase immune cell entry into the central nervous system 4 . We hypothesize that the TWD led to a hyper-responsive immune system that enhanced the hypersensitivity and prolonged the recovery from inflammatory pain induction.…”
Section: Discussionmentioning
confidence: 85%
“…57 Worse stroke outcome has also been confirmed in diet-induced models in which animals become obese due to being fed a high-fat diet. These detrimental effects of a high-fat diet have been observed in rat, 58,61,65,73,82,93 mouse 60,64,66,88 and gerbil 62,63,94 models of diet-induced obesity. A variety of models of cerebral ischaemia have also been used in these studies, including transient and permanent occlusion of the middle cerebral artery, common carotid artery ligation and exposure to a low-oxygen environment.…”
Section: Experimental Stroke In Obese Rodentsmentioning
confidence: 99%
“…In mice, it has recently been shown that the negative impact of diet-induced obesity on stroke outcome in mice is dependent on how long the obese phenotype is present and the severity of the initial stroke insult (length of ischaemia). 60 It is also unclear whether the detrimental effects of obesity on outcome in these preclinical studies are permanent, or reversible with weight loss. …”
Section: Experimental Stroke In Obese Rodentsmentioning
confidence: 99%
See 2 more Smart Citations